Feeding ecology and food preferences of Tachypleus gigas from Malaysian waters - Hajisamae, Sukree; John, Akbar; Nelson, Bryan R. (2019)
Horseshoe crabs are opportunistic foragers that can take advantage of a wide range of locally available prey. However, in the wild habitat, they prefer to feed on preferential food over other available feeds. Gut content analysis of Tachypleus gigas collected from east coast of Peninsular Malaysia showed monthly and seasonal variations in the food preferences of T. gigas. They prefer lesser number of polychaetes than bivalves during non-monsoon while it was the reverse during monsoon. Gut content analysis revealed that mollusks were highly preferred by T. gigas. It was also found that horseshoe crabs feed intensely during their peak mating season (May-August )in Pahang coast. Male prefers to feed less compared to the female crabs. In this study we also addressed electivity index (EI) and Gastro Somatic Index (GSI) of the crabs collected during 12 months of the sampling period .